EKSPERIMENTASI PEMBELAJARAN MATEMATIKA DENGAN MODEL PROBLEM BASED INSTRUCTION DAN GROUP INVESTIGATION PADA MATERI PECAHAN KELAS IV SD SE-KECAMATAN PANCUR DITINJAU DARI MINAT BELAJAR SISWA - -, Sumaji (Universitas Muria Kudus, 2014)
The Purpose of this reseach was to find out: (1) which model gives better learning achievement, group investigation, problem based instruction or direct model, (2) which students has better achievement, student with high interest in learning, middle, or low interest in learning, and (3) in each interest in learning, which model gives better learning achievement, group investigation learning model, problem based instruction, or direct one. Research method used was quasi experimental research with factorial 3x3. Research was held in 2012/2013 and the population was class IV students of SD in Pancur. Sample was taken by technique of Stratified Cluster Random Sampling. Data was collected by method of test, documentation and questionnaire. Before using those instruments, I tried out a test in Class IV SD Criwik. Test Instrument Analysis used content validity by experts judgment and reliability of test uses KR 20, and the test analysis consist of distinguishing and difficulty level. Questionnaire instrument test uses content validity by experts judgment, questionnaire reliability uses Cronbach Alpha, questionnaire analysis uses internal consistency test. Before data was analyzed, I do prerequisite test, that was a normality test with Liliefors method, and homogenitas test with Bartlett test. Technique of data analysis in this research uses two ways-Avana Analysis with the different cell, and it is continued by post hoc comparisons test with Scheffe method. Based on the data analysis, the results of this research are as follows. (1) Learning model of Problem Based Instruction gives better learning achievement of Mathematics than Group Investigation and the Direct one. Learning model of Group Investigation gives better learning achievement of Mathematics than direct leaning model, (2) Students with high interest in learning has better learning achievement of mathematics than students with middle interest in learning and the low one and students with middle interest in learning has better learning achievement of mathematics than students with the low one, and (3) The students with high, middle, and low interest in learning, learning model of Problem Based Instruction gives better learning achievement of mathematics than learning model of Group Investigation and the direct one and Learning model of Group Investigation gives better learning achievement than the direct one.